2018
DOI: 10.1016/j.jad.2018.07.078
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime affective problems and later-life cognitive state: Over 50 years of follow-up in a British birth cohort study

Abstract: HighlightsRecurrent lifetime affective problems predict diminished late-life cognitive state.Those with affective problems only once do not show risk of lower cognitive state.Recurrence, rather than timing, of problems is more predictive.These associations remain even when controlling for prior childhood cognition.The risk of lower cognitive state is already manifest in early old age (age 69).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 58 publications
2
28
0
5
Order By: Relevance
“…Educational attainment was defined as highest qualification on leaving full-time education in Whitehall II participants and by age 26 in NSHD participants. Depression caseness was defined using the General Health Questionnaire to ascertain depression symptoms, as previous operationalized by Goldberg and Hillier 23 and within the NSHD cohort by James et al 24 : scores of 5 or over (with the Likert scale recoded to 0-0-1-1 for each item before summing) were used as the threshold. For NSHD, covariates were taken from data collection at 60-64 years, the only wave with available cortisol measures available.…”
Section: Covariatesmentioning
confidence: 99%
“…Educational attainment was defined as highest qualification on leaving full-time education in Whitehall II participants and by age 26 in NSHD participants. Depression caseness was defined using the General Health Questionnaire to ascertain depression symptoms, as previous operationalized by Goldberg and Hillier 23 and within the NSHD cohort by James et al 24 : scores of 5 or over (with the Likert scale recoded to 0-0-1-1 for each item before summing) were used as the threshold. For NSHD, covariates were taken from data collection at 60-64 years, the only wave with available cortisol measures available.…”
Section: Covariatesmentioning
confidence: 99%
“…First, a structured modelling approach was used to compare a set of nested models corresponding to accumulation and sensitive period hypotheses to a saturated model including all main effects and all possible interactions. 8,27,28 The sensitive period model included three measures indicating whether an individual experienced caselevel affective symptoms at three time windows across the life course: early adulthood (age 23); middle adulthood (ages 33 and/or 42); and mid-life (age 50). The accumulation model included a measure of the number of time points (of the three windows of time described above) in which each individual experienced case-level affective symptoms.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…The first study 7 found no associations of affective symptoms measured between ages 13 to 53 with objectively measured cognitive outcomes at age 60-64, whereas the most recent study reported that persistent case-level affective symptoms were associated with poorer cognitive state, verbal memory and letter search speed and accuracy at age 69. 8 In this current study we tested for associations of affective symptoms across adulthood (ages 23, 33, 42 and 50) with aspects of cognitive function at age 50. Specifically, two complementary advanced statistical approaches were employed.…”
mentioning
confidence: 99%
“…Este estudio confirma la asociación entre depresión y deterioro cognitivo en personas mayores. Los hallazgos coinciden con una investigación de carácter longitudinal realizada en población británica, que concluye que problemas afectivos en el curso de la vida se asocian con un funcionamiento cognitivo disminuido en la adultez 8 . Por otra parte, un meta-análisis liderado por Rock et al en el año 2014, concluyó que el funcionamiento cognitivo disminuido se encontraba presente tanto en pacientes con diagnóstico actual de depresión, como en aquellos en remisión y en ausencia de sintomatología clínica de depresión 7 .…”
Section: Discussionunclassified
“…Al respecto existe abundante evidencia que indica que personas con diagnóstico de depresión muestran una disminución en sus funciones cognitivas, entre ellas atención, memoria y funciones ejecutivas [4][5][6][7] . Estudios de carácter longitudinal han concluido que problemas afectivos a lo largo de la vida predecirían un funcionamiento cognitivo disminuido en la adultez mayor 8 .…”
unclassified